Faktor-Faktor yang Mempengaruhi Struktur Modal - Suharsono Suharsono; Iwan Setiadi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
The purpose of this study was to determine the effect of Profitability, Liquidity, Asset Growth and Company Size on the Capital Structure of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2012-2018. The populationin this study uses food and beverage sub-sector companies. The total population of this study was 70 samples. The technique used in sampling is purposive sampling. The values tested in this thesis use the formula of financial ratios andregression analysis. The analysis shows profitability, liquidity, and asset growth have a significant negative effect on DER. While the size of the company (size) has a significant positive effect on DER. The test results show that return on assets(ROA), Current Ratio (CR), Asset Growth (Growth) and Firm Size (Size) together (simultaneously) have a significant effect on Debt to Equity Ratio (DER). Keywords: Profitability, Liquidity, Asset Growth, Company Size and Capital Structure.